Spontaneous Umbilical Endometriosis: A Case Report - Maharjan, Sailuja; Satyal, Bandana; Baidya, Reena (Europasian Journal of Medical Sciences, 2022)
Endometriosis is a common gynecological entity that usually occurs in the pelvic organs. Umbilical endometriosis is a rare condition that accounts for 0.5-1% of all extra genital endometriosis. It usually arises secondary to prior surgery but may arise de novo as well. We report a case of this condition with spontaneous occurrence, which was diagnosed preoperatively as umbilical granuloma. Umbilical endometriosis should be kept in differential diagnoses in women with umbilical lesions.